(untitled) (Web of Teachers: Inderscience Research, 2026)
Leukemia in children is a malignant disease of the blood characterized by the disruption of hematopoiesis in the bone marrow, leading to the replacement of normal blood cells with immature blast cells of the leukocyte lineage. The incidence of this disease is approximately 4–5 cases per 100,000 children. This article analyzes the clinical course of Acute Lymphoblastic Leukemia (ALL) in children and the primary prognostic factors influencing treatment outcomes. Research indicates that the accurate stratification of patients into risk groups based on age, sex, initial white blood cell (WBC) count, and cytogenetic characteristics is the key to enhancing therapeutic efficacy.